EFFECT OF BRAIN EXERCISE AND BENSON RELAXATION THERAPY ON DEPRESSION LEVEL IN THE ELDERLY IN THE ELDERLY SOCIAL SERVICE UNIT - Wulansari Wulansari; Ani Margawati; Rita Hadi W (Belitung Raya Foundation, Indonesia, 2018)
Background: Depression is one of the most common psychosocial problems in the elderly. The incidence of depression in the elderly is greater in the elderly living in the social service unit than the elderly in the community. Management of depression in the elderly should be more emphasized on interventions that focus on the individual needs of the biopsychosocial and spiritual aspects. Brain gym therapy and Benson relaxation are considered appropriate in decreasing depression. Objective: This study was to determine the effect of brain exercise and Benson relaxation on the level of depression in elderly in the elderly social service unit. Methods: This was a quasi-experimental study with pretest posttest control group design. Fifty-six elderly included in this study, which 28 assigned in the experiment and control group. The depression level was assessed using Geriatric Depression Scale (GDS). Wilcoxon and Mann-Whitney test were used for data analyses. Results: The study showed that the mean GDS score in the experiment group before the intervention was 7.21, while the mean value of GDS in the control group was 6.64. The mean value of GDS in the experiment group after the intervention was 5.04 and the mean in control group was 6.18. There was a significant difference of GDS score between experiment and control group with p-value of 0.021 (<0.05). Conclusion: There was a significant effect of brain gymnastics and Benson relaxation therapy in reducing depression in elderly. brain gymnastic therapy and Benson relaxation can be one of independent nursing interventions as an effort to improve care for elderly groups.